Analisis Sentimen Kenaikan Harga BBM pada Media Sosial Twitter - Iqbal Musyaffa; Mia Kamayani (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2022)
Based on information in a press conference at the Merdeka Palace on Saturday, 03 September 2022 at 14.30 WIB, President Joko Widodo has decreed that the price of fuel be officially raised. This is a burden for road users, especially users of two-wheeled vehicles. Currently, many people use social media sites to submit complaints regarding this topic. One of them social media Twitter. Therefore, sentiment analysis was carried out using 2 methods, namely the Naïve Bayes Classifier and the Decision Tree on 1100 tweets obtained from the keyword